1985
DOI: 10.1017/s0022112085003093
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional linear analysis of the compound jet

Abstract: The stability of an infinitely long compound liquid column is analysed by using a one-dimensional inviscid slice model. Results obtained from this one-dimensional linear analysis are applicable to the study of compound capillary jets, which are used in the ink-jet printing technique. Stability limits and the breaking regimes of such fluid configurations are established, and, whenever possible, theoretical results are compared with experimental ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 16 publications
4
23
0
Order By: Relevance
“…In their temporal analysis, these authors found two spatially unstable modes, stretching and squeezing, similar to those determined in previous studies. 47,48 They reported that the stretching mode yields a higher growth rate s, and thus would dominate the breakup dynamics if linear analysis were valid until pinch-off and the stretching mode were present in the initial perturbation. In their spatial analysis, they showed that the compound jet is unstable for small jet velocities and admits a convectively growing instability for larger velocities.…”
Section: Dynamics Of Compound Jetsmentioning
confidence: 99%
“…In their temporal analysis, these authors found two spatially unstable modes, stretching and squeezing, similar to those determined in previous studies. 47,48 They reported that the stretching mode yields a higher growth rate s, and thus would dominate the breakup dynamics if linear analysis were valid until pinch-off and the stretching mode were present in the initial perturbation. In their spatial analysis, they showed that the compound jet is unstable for small jet velocities and admits a convectively growing instability for larger velocities.…”
Section: Dynamics Of Compound Jetsmentioning
confidence: 99%
“…3, where the four solutions of (22) are shown, of which two are growing modes, which is similar to what is seen for an uniform inviscid compound jet, as found by Sanz and Meseguer. 1 Of the two unstable modes, it is typically assumed that breakup of the jet is caused by the mode with the largest growth rate and throughout this work we will focus our attention on this mode and we refer to it as the most unstable mode. In such a case, it can be seen that there is a value of the wavenumber k, at which the growth rate is maximal-we refer to this value as the most unstable wavenumber and denote it by k max .…”
Section: Resultsmentioning
confidence: 99%
“…6-10, for x = 0, is the same as illustrated in Sanz and Meseguer. 1 Using the results from our temporal instability analysis, we may determine the profile of waves travelling along both the inner and outer interfaces. In order to do this, we first need to evaluate an expression for timet (in Eqs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 There have also been linear stability studies that begin with model onedimensional equations, and perform a linear stability analysis of the simplified system. For example, Sanz and Meseguer 19 consider inviscid compound jets and write down a onedimensional model produced using the ideas of Lee. 20 The model is based on long wave asymptotics and raises certain consistency issues-for a consistent evaluation of such models as well as a comparison of solutions they produce; see Papageorgiou and Orellana.…”
Section: Introductionmentioning
confidence: 99%